Clinical, Diagnostic, and Imaging Findings in Three Juvenile Dogs With Paraspinal Hyperesthesia or Myelopathy as a Consequence of Hemophilia A: A Case Report - Fowler, Kayla M.; Bolton, Timothy A.; Rossmeisl, John H.; Arendse, Avril U.; Vernau, Karen M.; Li, Ronald H. L.; Parker, Rell L. (Frontiers in Veterinary Science, 2022)
Three juvenile dogs presented with an acute onset of paraspinal hyperesthesia and/or neurologic deficits. These dogs underwent anesthesia for MRI and additional diagnostics. The thoracolumbar MRI in Dog 1 revealed an accumulation of T2-weighted (T2W) hyperintense, T1-weighted (T1W) iso- to hyperintense, contrast enhancing extradural material. The differential diagnoses were meningitis with secondary hemorrhage or empyema or late subacute hemorrhage. The initial cervical MRI in Dog 2 revealed T1W meningeal contrast enhancement suspected to be secondary to meningitis. A repeat MRI following neurologic decline after CSF sampling revealed a large area of T2W and T1W hyperintensity between fascial planes of the cervical musculature as well as T2W iso- to hyperintense and T1W iso- to hypointense extradural material at the level of C1 consistent with hemorrhage. The cervical MRI in Dog 3 revealed T2W hyperintense and T1W iso- to hypointense extradural compressive material consistent with hemorrhage. Dogs 1 and 2 underwent CSF sampling and developed complications including subcutaneous hematoma and vertebral canal hemorrhage. Dog 3 underwent surgical decompression which revealed a compressive extradural hematoma. In each case, a hemophilia panel including factor VIII concentration confirmed the diagnosis of hemophilia A. Dog 1 had a resolution of clinical signs for approximately 5 months before being euthanized from gastrointestinal hemorrhage. Dog 2 was euthanized due to neurologic decompensation following CSF sampling. Dog 3 did well for 2 weeks after surgery but was then lost to follow-up. This case series provides information on clinical signs, MRI findings, and outcome in 3 juvenile dogs with hemophilia A that developed neurologic deficits or paraspinal hyperesthesia secondary to spontaneous or iatrogenic vertebral canal hemorrhage. Hemophilia A should be considered as a differential in any young dog presenting with an acute onset of hyperesthesia with or without neurologic deficits. This diagnosis should be prioritized in young male dogs that have other evidence of hemorrhage on physical exam.